Analisis Residu Profenofos dalam Tanah Secara Voltammetri Lucutan Menggunakan Elektroda Grafit - Tanik, Anita Florida (Jurnal Matematika dan Ilmu Pengetahuan Alam, 2015)
This study aimed to determine the ability of stripping voltammetry using graphite electrodes in analyzing profenofos. In this study, profenofos was accumulated at 0.3 V (V, vs Ag/AgCl) for 60 seconds at pH 5. Subsequently, the optimum conditions were used to analyze profenofos 10 ppb. The study yielded a correlation coefficient (r) of calibration curve of 0.9967; precision between of 95.69 â 99.14%; sensitivity of 32.64 Î¼A/ppb; detection limit of 0.0038 ppb and accuracy of 94 â 115%.Keywords : profenofos, graphite electrodes, voltammetry